GAMBARAN KESESUAIAN DAN KEBUTUHAN PELATIHAN PERAWAT DALAM PENINGKATAN KETERAMPILAN DI RS NYITDAH TABANAN - Listyowati, Rina; Raharjani, Ni Komang Sri Devi (ARCHIVE OF COMMUNITY HEALTH, 2024)
Nurses are one of the health workers who have a very important role in the hospital. Nurses are also health workers who have the most contact with patients, so they are required to have good skills and abilities in carrying out their duties. This study aims to describe the suitability and training needs of nurses in to improving skills at Nyitdah Tabanan Hospital. The design of this study were descriptive studies, with the aim to describe the suitability and training needs of nurses to improve the skills of nurses at Nyitdah Tabanan Hospital. The strategy used was a survey method which used a questionnaire as a data collection tool. The sampling technique used by Proportionate Stratified Random Sampling technique with a total sample of 70 respondents. Data analysis techniques were processed and described with univariate variables were explain the each characteristics of of the variables studied. The analysis in this study displays by the distribution of frequencies and percentages. The results of this study show an overview of the needs and suitability of nurse training at Nyitdah Tabanan Hospital. Nurse training at Nyitdah Tabanan Hospital has been carried out quite well. Whilst the training has a high level of need, it unfortunately has low participation rate. The training that was most needed by nurses with the highest percentage of needs is the Professional Nursing Practice Model Training (MPKP) and Emergency Management Training (PPGD). Management training at Nyitdah Tabanan Hospital is quite good. Keywords: Nurse, Training, PNPMT, EMT